Analysis of Food Hygiene, Sanitation Hygiene and Safety of Eating Equipment - Winata, Rivaldi Andika; Lemba, Lemba; Rahmadita, Ninda; Fadhillah, Hikmah; Malsyafinanti, Syarfina; Marlenywati, Marlenywati (Journal of Multidiscipline and Collaboration Research, 2024)
This study aims to assess food cleanliness, hygiene sanitation, and the safety of eating utensils in the canteens at Universitas Muhammadiyah Pontianak, specifically those serving buffet-style food. The research uses a quantitative method with a descriptive approach to describe the cleanliness and sanitation conditions in five canteens on campus. Data were collected through direct observations, interviews, and observation forms with canteen staff. The results show that most canteens have good levels of cleanliness and sanitation, with 80% of canteens receiving a "Good" rating for food cleanliness, although 20% require improvement. For hygiene sanitation, 40% of canteens received a "Good" rating, but 40% others need improvements, particularly in areas rated as "Poor." The assessment of eating utensil safety shows that most canteens meet good safety standards. However, some canteens, especially Kantin Mas Bian, need to improve utensil storage, as it received a "Does Not Meet Standards" score. Overall, the results of this study indicate that the cleanliness, sanitation, and safety of eating utensils in the canteens at Universitas Muhammadiyah Pontianak are good, but there is still room for improvement, particularly in sanitation management and utensil storage to support the health and comfort of the campus community.